Nilai-Nilai Pancasila di sekolah Dasar - Ahmad Arif Fadilah; Al Gifari; Alicia Ivanna (Cahaya Ilmu Bangsa Institute, 2025)
This research discusses elementary schools because there have been many research incidents. Pancasila is the ideology of the Indonesian state, and Pancasila is the standard or guideline of life for citizens, which is the daily behavior of Indonesian society and is clearly reflected in the Pancasila precepts. This research discusses the education of Pancasila values ​​as well as the efforts and importance of teaching. At this time, it is important to teach Pancasila values. This is about teaching Pancasila values ​​in elementary schools. Pancasila values ​​are values ​​that reflect and new behavior towards the values ​​contained in Pancasila in society. This is based on a library research approach where the author collects data and information in the form of documents, discussion books, journals, articles, etc.